Financial system reform in Trinidad and Tobago : realizing the vision - Swan-Daniel, Sandrs ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2004)
Outlines and reviews the key proposals for financial sector reform, as addressed in the Government's White Paper on the 'Reform of the Financial System of Trinidad and Tobago', which was laid in Parliament on June 30 2004. Explores the political economy of financial sector reform as prescribed in the White Paper and assesses the magnitude of the proposed changes to the financial system architecture.\n t